University education and professional ethics at work. Perception of students and teachers of administrative careers of the university Simón Bolívar sede del litoral (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
A combination of requirements, competences and qualities can define a good professional at work and when it comes to jobs specifically for professionals, a set of knowledge, skills and abilities acquired by the individual from birth are commonly demanded, influenced mostly by professionals. family values, school, academics and with those obtained within organizations. In this respect, university education has a very important role in the creation of the professional character of the worker, with the ethics of the individuals being developed in this document with a view to describing the importance of university education in the formation of the ethics for the exercise of the profession. The research is carried out in a population of students of the Simón Bolívar University, located on the coast, composed of 726 students distributed in the administrative courses Tourism Administration, Transportation Administration, Business Organization and Customs Administration, through a questionnaire to a representative sample of the students during the year 2016 and to a representative sample of professors of the aforementioned administrative careers. In Venezuela, according to the Magna Carta, education is a right based on the ethical valuation of work, this assertion seems to begin to reveal the legal importance that ethics has in training in the teaching and learning processes, however the fulfillment of This right depends to a large extent on the ethical commitment and vocation of teachers and educational institutions